2015
DOI: 10.3324/haematol.2014.123018
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and methylation analysis of preleukemic promyelocytes indicate a dual role for PML/RARA in leukemia initiation

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nPML/RARA preleukemic myeloid precursors eventually give rise to leukemic promyelocytes. Methods Murine model and bone marrow harvestMRP8-PML/RARA transgenic mice have been described elsewhere. 3 Mice were bred and maintained at the University of California, San Francisco under standard conditions. For each individual sample, bones from one male and one female were pooled, thoroughly cleaned, ground and filtered. Cells were collected after centrifugation on Histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…PML NBs also modulate E2F signaling (Vernier and Ferbeyre 2014). Thus, although the first models of oncogenic transformation by PML/RARA stressed the importance of the differentiation arrest through transcriptional silencing, recent studies have highlighted the central role of PML/RARA-mediated disruption of NBs and resulting proliferation boost (Occhionorelli et al 2011;Gaillard et al 2015).…”
Section: Acute Promyelocytic Leukemiamentioning
confidence: 99%
“…PML NBs also modulate E2F signaling (Vernier and Ferbeyre 2014). Thus, although the first models of oncogenic transformation by PML/RARA stressed the importance of the differentiation arrest through transcriptional silencing, recent studies have highlighted the central role of PML/RARA-mediated disruption of NBs and resulting proliferation boost (Occhionorelli et al 2011;Gaillard et al 2015).…”
Section: Acute Promyelocytic Leukemiamentioning
confidence: 99%
“…Acute promyelocytic leukemia (APL) is marked by the accumulation of promyelocytes due to a blockade of differentiation coupled with unlimited expansion. Approximately 97% of patients with APL express the promyelocytic leukemia/retinoic acid receptor a (PML/RARA) fusion protein as a result of t(15;17) (q22;q11.2), and although the paradigm has long suggested that PML/RARA is a potent repressor of key myeloid maturation genes, we recently challenged this model, 1 reopening fundamental questions as to the precise contribution of the fusion protein to leukemic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…18 By dimerizing and associating with an altered set of co-factors the DNA binding specificity and repressive ability of the fusion protein is expanded, 19 a characteristic that is believed to play a key role in the leukemogenic process. PML/RARA has been shown to interact with key transcription factors of the granulocytic differentiation program, such as PU.1 20 and C/EBPα downregulation has been observed in PML/RARA expressing cells, 21,22 both events possibly participating in the transformation process. Interestingly, TRIB1 has been shown to co-localize with RARA/RXR leading to negative regulation of the transcriptional activity of the complex, 23 although the precise mechanism mediating this inhibition is still unclear.…”
Section: Introductionmentioning
confidence: 99%